Environmental assessment for sustainable development (Ministry of Foreign Affairs, Danida, 1999)
Guidance on environmental assessment up to the approval stage programme support. Guidance on environmental assessment after the approval stage of sector programme support. Further guidance the environmental assessment process. Sectoral guidance notes.